Experimental Study of a Flexible Rotor and its Dependency on the Rolling-Bearing Temperature (International Journal of Rotating Machinery)
An experimental study of the effects of the bearing temperature on rotor unbalance responses and on the first forward and backward critical speeds is presented. Experimental tests consisted in run-ups and run-downs are realized to a flexible rotor developed and built at the Laboratoire de Tribologie et Dynamique des Systèmes, UMR CNRS 5513, École Centrale de Lyon, France. This flexible rotor is supported by two rolling bearings on flexible supports. It will be demonstrated that rolling-element bearing temperature has no-negligible effects of the amplitude and values of the forward and backward first critical speeds of the flexible rotor. In addition to the investigation of the influences of the bearing temperature on the dynamics of the flexible rotor at the first critical speeds, a brief investigation into the complete dynamic within the speed range of interest is also conducted. The purpose of this is to examine in detail the vibrational phenomena of the flexible rotor and to detect some characteristics dynamic behaviour due to the presence of rolling-element bearings.